2021
DOI: 10.12669/pjms.37.7.4257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tadalafil combined with atorvastatin on hemodynamics and sexual function in middle-aged and elderly patients with hyperlipidemia complicated with erectile dysfunction

Abstract: Objective: To evaluate the effect and clinical significance of tadalafil combined with atorvastatin on hemodynamics and sexual function in middle-aged and elderly patients with hyperlipidemia complicated with Erectile dysfunction (ED). Methods: Eighty patients with hyperlipidemia complicated with ED who were treated at The Second Hospital of Hebei Medical University from January 2019 to June 2020 were selected. Using a completely randomized design experimental method, these 80 patients were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Three hundred and seventy‐eight related studies were found from all databases, and 9 studies were finally included in this meta‐analysis after subsequent screenings (Bank et al, 2006; Dadkhah et al, 2010; Doğru et al, 2008; Du et al, 2021; El‐Sisi et al, 2013; Gokce et al, 2012; Gokkaya et al, 2008; Herrmann et al, 2006; Nurkalem et al, 2014). Figure 1 depicts the method of screening the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three hundred and seventy‐eight related studies were found from all databases, and 9 studies were finally included in this meta‐analysis after subsequent screenings (Bank et al, 2006; Dadkhah et al, 2010; Doğru et al, 2008; Du et al, 2021; El‐Sisi et al, 2013; Gokce et al, 2012; Gokkaya et al, 2008; Herrmann et al, 2006; Nurkalem et al, 2014). Figure 1 depicts the method of screening the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the nine selected papers were RCTs (Bank et al, 2006; Dadkhah et al, 2010; Du et al, 2021; El‐Sisi et al, 2013; Gokce et al, 2012; Herrmann et al, 2006; Nurkalem et al, 2014) and two were non‐randomized studies (Doğru et al, 2008; Gokkaya et al, 2008). 332 patients received an atorvastatin treatment, 141 patients received a placebo treatment, 44 patients received a rosuvastatin treatment and 40 patients received a combination of atorvastatin and tadalafil treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies as well as many clinical trials reported that TAD has different beneficial effects in multiple diseases regarding hyperglycemia [ 24 ], inflammation [ 25 ], oxidative stress [ 26 ] and endothelial dysfunction [ 27 ] that make it a target in treatment or at least as adjuvant therapy for multiple diseases. PTX has recently reported various beneficial effects on the kidneys directly [ 28 ].…”
Section: Discussionmentioning
confidence: 99%